Improved photovoltaic performance of multiple carbon-doped ZnO nanostructures under UV and visible light irradiation - Liu, Xianbin (2014)
We report synthesis of multiple carbon-doped ZnO nanostructures by using carbon cloth as substrates to obtain multiple hollow ZnO microtube-nanowire structures. X-ray diffraction, X-ray photoelectron spectroscopy, and transmission electron microscopy analysis clearly show that carbon is doped into ZnO through substitution of carbon for oxygen in the growth and annealing processes. Upon exposure to 633-nm red laser, a distinct photoresponse can be observed, which indicates that carbon doping in ZnO can well extend its light harvesting to visible light region. Furthermore, a prototype of photovoltaic cell was fabricated to demonstrate the photovoltaic performance of multiple carbon-doped ZnO nanostructures under UV and visible light irradiation. This result shows that carbon-doped ZnO can act as effective photoactive materials for photoelectric components.